High-strength anti-bending aluminum-based copper-clad plate and preparation method thereof

By using a combination of fiber-reinforced resin composite material and aluminum alloy in aluminum-based copper clad plate, the problems of low strength and poor bending resistance of aluminum-based copper clad plate are solved, and higher strength and bending resistance are achieved.

CN119427858APending Publication Date: 2025-02-14HENAN ACAD OF SCI INST OF APPLIED PHYSICS CO LTD

Patent Information

Application Number
CN202411609969.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing aluminum-based copper clad plate has low strength during use and has poor bending resistance. It is easy to bending during installation or use, which affects the use effect.

Method used

Using two layers of copper foil to fill fiber-reinforced resin composite material, the embedded aluminum alloy is fixed in the fiber-reinforced resin composite material. Through the combination of carbon fiber, glass fiber, nanotitanium dioxide and resin, the strength and bending resistance of aluminum-based copper clad plate are improved. ability.

Benefits of technology

The strength and bending resistance of aluminum-based copper clad plate are significantly improved, and the problems of low strength and poor bending resistance in the existing technology are solved, which improves the use effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119427858A_ABST
    Figure CN119427858A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum-based copper-clad plates, in particular to a high-strength anti-bending aluminum-based copper-clad plate and a preparation method thereof.The high-strength anti-bending aluminum-based copper-clad plate comprises two layers of copper foils, the space between the two layers of copper foils is filled with a fiber-reinforced resin composite material, and aluminum alloy is fixedly embedded in the fiber-reinforced resin composite material. According to the high-strength anti-bending aluminum-based copper-clad plate and the preparation method thereof, grafting modification is performed on the surfaces of the glass fibers and the carbon fibers, so that the adhesion and wettability of the surfaces of the glass fibers and the carbon fibers can be improved, and nano titanium dioxide particles can be adsorbed on the surfaces of the glass fibers and the carbon fibers; according to the preparation method, the glass fibers and the carbon fibers can be linearly adhered, so that the carbon fibers, the glass fibers and the nano titanium dioxide linearly form a compound, and then the compound is adhered to the alloy aluminum and the copper foil by using the resin as a carrier, so that the strength and the bending resistance of the prepared aluminum-based copper-clad plate are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum-based copper-clad laminates, and in particular to a high-strength, bending-resistant aluminum-based copper-clad laminate and a preparation method thereof. Background Art

[0002] Aluminum-based copper-clad laminate is an aluminum substrate, which is a kind of raw material. It is a plate-shaped material made of electronic glass fiber cloth or other reinforcing materials impregnated with resin, single resin, etc. as an insulating adhesive layer, covered with copper foil on one or both sides and hot pressed. It is called copper-clad foil laminated aluminum substrate, referred to as aluminum-based copper-clad laminate. High-strength anti-bending aluminum-based copper-clad laminate, as a special electronic material, not only has excellent conductive properties, but also has excellent anti-bending properties. The aluminum-based copper-clad laminate is based on electronic glass fiber cloth or other reinforcing materials, impregnated with insulating adhesive layers such as resin, covered with copper foil on one or both sides, and hot pressed by a special process. As a substrate material in the manufacture of printed circuit boards, aluminum-based copper-clad laminates mainly play the role of interconnection, insulation and support for printed circuit boards, and have a great influence on the transmission speed, energy loss and characteristic impedance of signals in the circuit. The performance, quality, processability in manufacturing, manufacturing level, manufacturing cost, and long-term reliability and stability of printed circuit boards depend to a large extent on aluminum-based copper-clad laminates. The aluminum-based copper-clad laminate manufacturing industry is a sunrise industry. It has broad development prospects along with the development of copper-clad aluminum substrates in the electronic information and communication industries. Its manufacturing technology is a high-tech that crosses, penetrates and promotes multiple disciplines. It develops synchronously with the electronic information industry, especially the printed circuit industry, and is inseparable. Its progress and development have always been driven by the innovation and development of electronic complete products, semiconductor manufacturing technology, electronic installation technology and printed circuit board manufacturing technology. There are generally three types of aluminum-based copper-clad laminates: one is a relatively low thermal conductivity of 1.0; the second is a medium thermal conductivity of 1.5; the third is the highest thermal conductivity above 2.0.

[0003] However, the aluminum-based copper-clad laminates of the prior art have the following problems in actual use: The strength is low and the bending resistance is poor. It often bends during use or installation, thus affecting the use effect. To solve this problem, a high-strength and bending-resistant aluminum-based copper-clad laminate and a preparation method thereof are provided. Summary of the invention

[0004] The purpose of the present invention is to provide a high-strength and anti-bending aluminum-based copper-clad laminate and a preparation method thereof to solve the problems raised in the above background technology. To achieve the above purpose, the present invention provides the following technical solution: a high-strength and anti-bending aluminum-based copper-clad laminate, comprising two layers of copper foil, a fiber-reinforced resin composite material is filled between the two layers of copper foil, and an aluminum alloy is fixedly embedded in the fiber-reinforced resin composite material.

[0005] A method for preparing high-strength and anti-bending aluminum-based copper clad material comprises the following steps: S1. Prepare corresponding molds according to the shape and size of the composite product; S2, cutting the two layers of copper foil into the required shape and size according to the design requirements, and laying one layer of the copper foil flat on the bottom of the inner cavity of the mold; S3, mixing the fiber-reinforced resin composite material and the acid anhydride curing agent in proportion, and pouring the mixed fiber-reinforced resin composite material into the mold, wherein the liquid level of the fiber-reinforced resin composite material is located in the middle of the inner cavity of the mold; S4, placing the aluminum alloy in the middle of the mold and above the fiber-reinforced resin composite material, and then adding the fiber-reinforced resin composite material into the mold until the mold is filled; S5, laminating another layer of copper foil on the fiber reinforced resin composite material; S6. According to the curing conditions of the fiber-reinforced resin composite material, heat the mold to a temperature of 170-180 degrees Celsius for 20-30 minutes to cure the fiber-reinforced resin composite material. After curing, take out the composite material product and perform necessary trimming and polishing.

[0006] Preferably, the fiber-reinforced resin composite material comprises: 10 parts of epoxy resin, 10 parts of amide, 2 parts of acetone, 1 part of glass fiber, 1 part of nano-titanium dioxide, and 1 part of carbon fiber.

[0007] Preferably, the preparation of the fiber-reinforced resin composite material further comprises: S31, weighing the epoxy resin and the amide according to a proportion, and placing them in a glass container, adding acetone according to a proportion, and stirring continuously with a glass rod until the epoxy resin is completely dissolved into a crystal clear liquid with strong fluidity; S32, placing the container containing the liquid in a water bath and subjecting it to high temperature treatment for 20 minutes to volatilize the residual acetone in the liquid; S33, placing the container in a vacuum box for vacuum treatment to remove bubbles to prepare a resin material; S34, preparing a composite fiber material by using glass fiber, nano titanium dioxide and carbon fiber in a certain proportion; S35, adding the composite fiber material to the resin material and stirring evenly to prepare a fiber-reinforced resin composite material.

[0008] Preferably, the method for preparing the composite fiber material further comprises: S341, prepare functionalized POSS nanoparticle solution, impregnate glass fiber in silane coupling agent solution, dry and remove water to obtain silanized glass fiber, add initiator to the prepared functionalized POSS nanoparticle solution, then add silanized glass fiber, wash off the remaining solution after impregnation, and obtain graft-modified glass fiber after drying; S342, cleaning and drying the surface of the carbon fiber, irradiating the carbon fiber with high-energy radiation to generate irradiation active points, adding oligomers to the irradiation active points to make the oligomers less than zero have a grafting effect with the active points to prepare grafted modified carbon fibers; S343, mixing and stirring the graft-modified glass fiber and the graft-modified carbon fiber prepared in S341 and S342 at a temperature of 200-300 degrees Celsius to form a composite; S344, using a pulverizer to grind nano titanium dioxide into fine particles with a diameter of 10-20 nanometers and adding the particles to the composite prepared in S343, so that the particles are attached to the connection points of the composite to prepare composite A; S345, adding the composite A to the resin material and mixing them evenly to prepare a fiber-reinforced resin composite material.

[0009] Preferably, the high-energy radiation includes gamma rays, beta rays, and electron beams.

[0010] Preferably, the initiator is one or more of sodium bisulfite, potassium bisulfite and azobisisobutyronitrile.

[0011] Preferably, a cationic surfactant is further added to S341, and the cationic surfactant is a nitrogen-containing morpholine ring, pyridine ring, imidazole ring, piperazine ring and quinoline ring.

[0012] Preferably, the mass ratio of the functionalized POSS nanoparticles to the glass fibers in S341 is 4-40%.

[0013] Preferably, in the S341, the mass ratio of the silane coupling agent to the functionalized POSS nanoparticles is 0.4-4%, and the molar ratio of the initiator to the functionalized POSS nanoparticles is 0.5-6%.

[0014] Compared with the prior art, the present invention has the following beneficial effects: In this case, the fiber-reinforced resin composite material prepared by carbon fiber, glass fiber, nano-titanium dioxide and resin is used to connect and fill the aluminum alloy and copper foil, which can improve the strength and bending resistance of the aluminum-based copper-clad laminate, and solve the problem that the aluminum-based copper-clad laminate in the prior art has low strength and poor bending resistance in actual use, and often bends during use or installation, thereby affecting the use effect; By grafting and modifying the surfaces of glass fibers and carbon fibers, the adhesion and wettability of the surfaces of glass fibers and carbon fibers can be improved, so that nano-titanium dioxide particles can be adsorbed on the surfaces of glass fibers and carbon fibers, and the glass fibers and carbon fibers can be straightly adhered to each other, thereby forming a straight line of carbon fibers, glass fibers, and nano-titanium dioxide. Resin is then used as a carrier to adhere them to alloy aluminum and copper foil, thereby improving the strength and bending resistance of the prepared aluminum-based copper-clad laminate. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 A schematic diagram of the three-dimensional structure of a high-strength, anti-bending aluminum-based copper-clad laminate and a preparation method thereof of the present invention; Figure 2 It is a structural schematic diagram of an aluminum-based copper-clad laminate with high strength and anti-bending properties and a preparation method thereof of the present invention; Figure 3 This is an electron microscope image of a high-strength, anti-bending aluminum-based copper-clad laminate and a preparation method thereof of the present invention, and copper foil and glass fiber; Figure 4 This is an electron microscope image of carbon fiber of a high-strength, anti-bending aluminum-based copper-clad laminate and a preparation method thereof of the present invention; Figure 5 This is an electron microscope image of nano-titanium dioxide in a high-strength, bending-resistant aluminum-based copper-clad laminate of the present invention.

[0016] In the figure: 1. Copper foil, 2. Fiber-reinforced resin composite material, 3. Aluminum alloy. DETAILED DESCRIPTION

[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technical personnel in this field without creative work are within the scope of protection of the present invention.

[0018] Example 1 See also Figures 1 to 5The present invention provides a technical solution: a high-strength and anti-bending aluminum-based copper-clad laminate, comprising two layers of copper foil 1, a fiber-reinforced resin composite material 2 is filled between the two layers of copper foil 1, an aluminum alloy 3 is fixedly embedded in the fiber-reinforced resin composite material 2, and the aluminum alloy 3 and the copper foil 1 are connected and filled with the fiber-reinforced resin composite material 2 prepared by carbon fiber, glass fiber, nano-titanium dioxide and resin, which can improve the strength and anti-bending ability of the aluminum-based copper-clad laminate, and solve the problem that the aluminum-based copper-clad laminate in the prior art has low strength and poor anti-bending ability during actual use, and often bends during use or installation, thereby affecting the use effect.

[0019] A method for preparing high-strength and anti-bending aluminum-based copper clad material comprises the following steps: S1. Prepare corresponding molds according to the shape and size of the composite product; S2, cutting the two layers of copper foil 1 into the required shape and size according to the design requirements, and laying one layer of the copper foil 1 flat on the bottom end of the inner cavity of the mold; S3, mixing the fiber-reinforced resin composite material 2 and the acid anhydride curing agent in proportion, and pouring the mixed fiber-reinforced resin composite material 2 into the mold, wherein the liquid level of the fiber-reinforced resin composite material 2 is located in the middle of the mold cavity, and the addition of the acid anhydride can play a curing role, which can facilitate the curing of the resin; S4, placing the aluminum alloy 3 in the middle of the mold and above the fiber-reinforced resin composite material 2, and then adding the fiber-reinforced resin composite material 2 into the mold until the mold is filled; S5, pasting another layer of copper foil 1 on the fiber reinforced resin composite material 2; S6. According to the curing conditions of the fiber-reinforced resin composite material 2, the mold is heated to 170 degrees Celsius for 20 minutes to cure the fiber-reinforced resin composite material 2. After curing, the composite material product is taken out and necessary trimming and polishing are performed. The resin can be fully cured by heating at 170 degrees Celsius for 20 minutes.

[0020] In this embodiment, the fiber-reinforced resin composite material 2 includes: 10 parts of epoxy resin, 10 parts of amide, 2 parts of acetone, 1 part of glass fiber, 1 part of nano titanium dioxide, and 1 part of carbon fiber. Glass fiber (Fiberglass) is an inorganic non-metallic material with excellent performance and a wide variety. Its advantages are good insulation, strong heat resistance, good corrosion resistance, and high mechanical strength, but its disadvantages are brittleness and poor wear resistance. It is made of six kinds of minerals, namely pyrophyllite, quartz sand, limestone, dolomite, colemanite, and magnesia stone, through high-temperature melting, wire drawing, winding, weaving and other processes. The diameter of its single filament is from several microns to more than twenty microns, which is equivalent to 1 / 20-1 / 5 of a hair. Each bundle of fiber strands is composed of hundreds or even thousands of single filaments. Glass fiber is usually used as reinforcing material in composite materials, electrical insulation materials and thermal insulation materials, circuit substrates and other fields of the national economy. Nano titanium dioxide is a white loose powder with strong ultraviolet shielding effect and good dispersibility and weather resistance. Nano-TiO2 has very valuable optical properties and shows a bright future in the automotive industry and many other fields. Nano-TiO2 also has high chemical stability, thermal stability, super hydrophilicity, and non-migration, so it is widely used in anti-ultraviolet materials, textiles, photocatalytic catalysts, self-cleaning glass, sunscreens, coatings, inks, food packaging materials, papermaking industry, aerospace industry, and lithium batteries. Carbon fiber is mainly composed of carbon elements and has the characteristics of high temperature resistance, friction resistance, thermal conductivity, and corrosion resistance. It is fibrous, soft, and can be processed into various fabrics. Because its graphite microcrystalline structure is preferentially oriented along the fiber axis, it has high strength and modulus along the fiber axis. Carbon fiber has a low density, so it has high specific strength and specific modulus. The main use of carbon fiber is to be used as a reinforcing material and compounded with resins, metals, ceramics, and carbon to manufacture advanced composite materials. Carbon fiber reinforced epoxy resin composites have the highest specific strength and specific modulus among existing engineering materials.

[0021] In this embodiment, the preparation of the fiber-reinforced resin composite material 2 further includes: S31, the epoxy resin and the amide are weighed in proportion and loaded into a glass container, acetone is added in proportion, and the mixture is continuously stirred with a glass rod until the epoxy resin is completely dissolved into a crystal clear liquid with strong fluidity. The addition of acetone can increase the fusion speed between the resin and the amide, and acetone is volatile; S32, placing the container containing the liquid in a water bath and subjecting it to high temperature treatment for 20 minutes to volatilize the residual acetone in the liquid; S33, placing the container in a vacuum box for vacuum treatment to remove bubbles to prepare a resin material; S34, preparing a composite fiber material by using glass fiber, nano titanium dioxide and carbon fiber in a certain proportion; S35, adding the composite fiber material to the resin material and stirring evenly to prepare a fiber-reinforced resin composite material 2.

[0022] In this embodiment, the method for preparing the composite fiber material further includes: S341, prepare functionalized POSS nanoparticle solution, impregnate glass fiber in silane coupling agent solution, dry and remove water to obtain silanized glass fiber, add initiator to the prepared functionalized POSS nanoparticle solution, then add silanized glass fiber, wash off the remaining solution after impregnation, and obtain graft-modified glass fiber after drying; S342, cleaning and drying the surface of the carbon fiber, irradiating the carbon fiber with high-energy radiation to generate irradiation active points, adding oligomers to the irradiation active points to make the oligomers less than zero have a grafting effect with the active points to prepare grafted modified carbon fibers; S343, mixing and stirring the graft-modified glass fiber and the graft-modified carbon fiber prepared in S341 and S342 at a temperature of 200-300 degrees Celsius to form a composite; S344, using a pulverizer to grind nano titanium dioxide into fine particles with a diameter of 10 nanometers and adding the particles to the composite prepared in S343, so that the particles are attached to the connection points of the composite to prepare composite A; S345, adding the composite A to the resin material and mixing them evenly to prepare the fiber-reinforced resin composite material 2.

[0023] In this embodiment, the high-energy radiation includes gamma rays, beta rays, and electron beams.

[0024] In this embodiment, the initiator is one or more of sodium bisulfite, potassium bisulfite and azobisisobutyronitrile.

[0025] In this embodiment, a cationic surfactant is further added in S341, and the cationic surfactant is a nitrogen-containing morpholine ring, pyridine ring, imidazole ring, piperazine ring and quinoline ring.

[0026] In this embodiment, the mass ratio of the functionalized POSS nanoparticles to the glass fibers in S341 is 4%.

[0027] In this embodiment, the mass ratio of the silane coupling agent to the functionalized POSS nanoparticles in S341 is 0.4%, and the molar ratio of the initiator to the functionalized POSS nanoparticles is 0.5%.

[0028] Example 2 See also Figures 1 to 5The present invention provides a technical solution: a high-strength, bending-resistant aluminum-based copper-clad laminate, comprising two layers of copper foil 1, a fiber-reinforced resin composite material 2 is filled between the two layers of copper foil 1, and an aluminum alloy 3 is fixedly embedded in the fiber-reinforced resin composite material 2.

[0029] A method for preparing high-strength and anti-bending aluminum-based copper clad material comprises the following steps: S1. Prepare corresponding molds according to the shape and size of the composite product; S2, cutting the two layers of copper foil 1 into the required shape and size according to the design requirements, and laying one layer of the copper foil 1 flat on the bottom end of the inner cavity of the mold; S3, mixing the fiber-reinforced resin composite material 2 and the acid anhydride curing agent in proportion, and pouring the mixed fiber-reinforced resin composite material 2 into the mold, wherein the liquid level of the fiber-reinforced resin composite material 2 is located in the middle of the mold cavity; S4, placing the aluminum alloy 3 in the middle of the mold and above the fiber-reinforced resin composite material 2, and then adding the fiber-reinforced resin composite material 2 into the mold until the mold is filled; S5, pasting another layer of copper foil 1 on the fiber reinforced resin composite material 2; S6. According to the curing conditions of the fiber-reinforced resin composite material 2, the mold is heated to 180 degrees Celsius for 30 minutes to cure the fiber-reinforced resin composite material 2. After curing, the composite material product is taken out and necessary trimming and polishing is performed.

[0030] In this embodiment, the fiber-reinforced resin composite material 2 includes: 10 parts of epoxy resin, 10 parts of amide, 2 parts of acetone, 1 part of glass fiber, 1 part of nano titanium dioxide, and 1 part of carbon fiber.

[0031] In this embodiment, the preparation of the fiber-reinforced resin composite material 2 further includes: S31, weighing the epoxy resin and the amide according to a proportion, and placing them in a glass container, adding acetone according to a proportion, and stirring continuously with a glass rod until the epoxy resin is completely dissolved into a crystal clear liquid with strong fluidity; S32, placing the container containing the liquid in a water bath and subjecting it to high temperature treatment for 20 minutes to volatilize the residual acetone in the liquid; S33, placing the container in a vacuum box for vacuum treatment to remove bubbles to prepare a resin material; S34, preparing a composite fiber material by using glass fiber, nano titanium dioxide and carbon fiber in a certain proportion; S35, adding the composite fiber material to the resin material and stirring evenly to prepare a fiber-reinforced resin composite material 2.

[0032] In this embodiment, the method for preparing the composite fiber material further includes: S341, prepare functionalized POSS nanoparticle solution, impregnate glass fiber in silane coupling agent solution, dry and remove water to obtain silanized glass fiber, add initiator to the prepared functionalized POSS nanoparticle solution, then add silanized glass fiber, wash off the remaining solution after impregnation, and obtain graft-modified glass fiber after drying; S342, cleaning and drying the surface of the carbon fiber, irradiating the carbon fiber with high-energy radiation to generate irradiation active points, adding oligomers to the irradiation active points to make the oligomers less than zero have a grafting effect with the active points to prepare grafted modified carbon fibers; S343, mixing and stirring the graft-modified glass fiber and the graft-modified carbon fiber prepared in S341 and S342 at a temperature of 300 degrees Celsius to form a composite; S4, using a pulverizer to grind nano titanium dioxide into fine particles with a diameter of 20 nanometers and adding the particles to the composite prepared in S343, so that the particles are attached to the connection points of the composite to prepare composite A; S5. Add the composite A to the resin material and mix them evenly to prepare the fiber-reinforced resin composite material 2.

[0033] In this embodiment, the high-energy radiation includes gamma rays, beta rays, and electron beams.

[0034] In this embodiment, the initiator is one or more of sodium bisulfite, potassium bisulfite and azobisisobutyronitrile.

[0035] In this embodiment, a cationic surfactant is further added in S341, and the cationic surfactant is a nitrogen-containing morpholine ring, pyridine ring, imidazole ring, piperazine ring and quinoline ring.

[0036] In this embodiment, the mass ratio of the functionalized POSS nanoparticles to the glass fibers in S341 is 40%.

[0037] In this embodiment, the mass ratio of the silane coupling agent to the functionalized POSS nanoparticles in S341 is 4%, and the molar ratio of the initiator to the functionalized POSS nanoparticles is 6%.

[0038] The above shows and describes the basic principles, main features and advantages of the present invention. Technical personnel in this industry should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not used to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A high-strength, anti-bending aluminum-based copper-clad laminate, comprising two layers of copper foil, characterized in that: A fiber-reinforced resin composite material is filled between the two layers of copper foil, and an aluminum alloy is fixedly embedded in the fiber-reinforced resin composite material.

2. A method for preparing high-strength and anti-bending aluminum-based copper clad material, characterized in that: The steps include: S1. Prepare corresponding molds according to the shape and size of the composite product; S2, cutting the two layers of copper foil into the required shape and size according to the design requirements, and laying one layer of the copper foil flat on the bottom of the inner cavity of the mold; S3, mixing the fiber-reinforced resin composite material and the acid anhydride curing agent in proportion, and pouring the mixed fiber-reinforced resin composite material into the mold, wherein the liquid level of the fiber-reinforced resin composite material is located in the middle of the inner cavity of the mold; S4, placing the aluminum alloy in the middle of the mold and above the fiber-reinforced resin composite material, and then adding the fiber-reinforced resin composite material into the mold until the mold is filled; S5, laminating another layer of copper foil on the fiber reinforced resin composite material; S6. According to the curing conditions of the fiber-reinforced resin composite material, heat the mold to a temperature of 170-180 degrees Celsius for 20-30 minutes to cure the fiber-reinforced resin composite material. After curing, take out the composite material product and perform necessary trimming and polishing.

3. The method for preparing a high-strength, anti-bending aluminum-based copper-clad laminate according to claim 2, characterized in that: The fiber-reinforced resin composite material comprises: 10 parts of epoxy resin, 10 parts of amide, 2 parts of acetone, 1 part of glass fiber, 1 part of nano titanium dioxide, and 1 part of carbon fiber.

4. The method for preparing a high-strength, anti-bending aluminum-based copper-clad laminate according to claim 3, characterized in that: The preparation of the fiber-reinforced resin composite material also includes: S31, weighing the epoxy resin and the amide according to a proportion, and placing them in a glass container, adding acetone according to a proportion, and stirring continuously with a glass rod until the epoxy resin is completely dissolved into a crystal clear liquid with strong fluidity; S32, placing the container containing the liquid in a water bath and subjecting it to high temperature treatment for 20 minutes to volatilize the residual acetone in the liquid; S33, placing the container in a vacuum box for vacuum treatment to remove bubbles to prepare a resin material; S34, preparing a composite fiber material by using glass fiber, nano titanium dioxide and carbon fiber in a certain proportion; S35, adding the composite fiber material to the resin material and stirring evenly to prepare a fiber-reinforced resin composite material.

5. The method for preparing a high-strength, anti-bending aluminum-based copper-clad laminate according to claim 4, characterized in that: The preparation method of the composite fiber material also includes: S341, prepare functionalized POSS nanoparticle solution, impregnate glass fiber in silane coupling agent solution, dry and remove water to obtain silanized glass fiber, add initiator to the prepared functionalized POSS nanoparticle solution, then add silanized glass fiber, wash off the remaining solution after impregnation, and obtain graft-modified glass fiber after drying; S342, cleaning and drying the surface of the carbon fiber, irradiating the carbon fiber with high-energy radiation to generate irradiation active points, adding oligomers to the irradiation active points to make the oligomers less than zero have a grafting effect with the active points to prepare grafted modified carbon fibers; S343, mixing and stirring the graft-modified glass fiber and the graft-modified carbon fiber prepared in S341 and S342 at a temperature of 200-300 degrees Celsius to form a composite; S344, using a pulverizer to grind nano titanium dioxide into fine particles with a diameter of 10-20 nanometers and adding the particles to the composite prepared in S343, so that the particles are attached to the connection points of the composite to prepare composite A; S345, adding the composite A to the resin material and mixing them evenly to prepare a fiber-reinforced resin composite material.

6. The method for preparing a high-strength, anti-bending aluminum-based copper-clad laminate according to claim 5, characterized in that: The high-energy radiation includes gamma rays, beta rays, and electron beams.

7. The method for preparing a high-strength, anti-bending aluminum-based copper-clad laminate according to claim 5, characterized in that: The initiator is one or more of sodium bisulfite, potassium bisulfite and azobisisobutyronitrile.

8. The method for preparing a high-strength, anti-bending aluminum-based copper-clad laminate according to claim 5, characterized in that: A cationic surfactant is also added to the S341, and the cationic surfactant is a nitrogen-containing morpholine ring, pyridine ring, imidazole ring, piperazine ring and quinoline ring.

9. The method for preparing a high-strength, anti-bending aluminum-based copper-clad laminate according to claim 5, characterized in that: The mass ratio of the functionalized POSS nanoparticles to the glass fibers in the S341 is 4-40%.

10. The method for preparing a high-strength, anti-bending aluminum-based copper-clad laminate according to claim 5, characterized in that: In the S341, the mass ratio of the silane coupling agent to the functionalized POSS nanoparticles is 0.4-4%, and the molar ratio of the initiator to the functionalized POSS nanoparticles is 0.5-6%.

Citation Information

Patent Citations

  • Resin composition and application thereof

    CN110903603A

  • Preparation method of high-modulus carbon fiber grafted glycidyl methacrylate

    CN115450047A

  • Glass fiber grafting modification method and application

    CN115521078A

  • Flexible aluminium base copper -clad plate

    CN206048933U

  • Processes for producing thermoplastic resins,crosslinked resins and crosslinked resin compositematerials

    KR1020050016909A

Cited By

  • High-strength and high-toughness PBT composite material and preparation method thereof

    CN122541956A